Integrated single-stage converters with Tri-state modulation suitable for photovoltaic systems - Galotto, Luigi [UNESP]; De Brito, Moacyr A.G. [UNESP]; Sampaio, Leonardo P. [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
The aim of this work is to present two topological simplified converters named Tri-state Boost and Tri-state Buck-Boost integrated single-phase inverters. An important operation capability can be achieved for these converters using a Tri-state Modulation control scheme. This is the inductive power decoupling and the independent input output control. These features are directly related with the photovoltaic micro-converter needs, improving efficiency, cost and mainly lifetime. These features for the proposed modulation are confirmed through experimental results. © 2011 IEEE.
Keywords: Integrated converter; Photovoltaic Systemsconverters; Power Decoupling; Single-Stage; Tri-State Modulation; Buck-boost; Control schemes; Improving efficiency; Input-output; Integrated converters; Photovoltaic systems; Single stage; Single stage converters; Single-phase inverters; Integration; Modulation; Photovoltaic effects; Power electronics; DC-DC converters